2011
DOI: 10.4238/vol10-3gmr997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of follicle-stimulating hormone beta polypeptide precursor cDNA from the bovine pituitary gland

Abstract: ABSTRACT. Follicle-stimulating hormone (FSH) plays an essential role in mammalian spermatogenesis and follicular development. In a previous study, we demonstrated that some bulls carry numerous linked mutations in the FSH beta-subunit (FSHB) gene, and that these bulls have poorquality semen, low fertility, and slightly lower serum FSH concentration compared to those without such mutations. Here, we identified the different FSHB mRNA transcripts in such individuals and analyzed the evolutionary pattern of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The genetic factors influence on production and sperm quality have been reported by several studies (Kim et al, 1988;Fries, 1989). Dai et al (2009) and Dai et al (2011) examined the gene polymorphism FSH beta-sub unit of production and sperm quality in Simmental, Charolais and Limousin. Some researchers also associate the diversity of FSH beta-sub unit genes with litter size in sow (Yaofeng et al, 1998;Li et al, 2000;Li et al, 2008;Liu et al, 2009), sperm quality in boar (Wimmer et al, 2005;Lin et al, 2006), litter size in ewes (Xiaopeng et al, 2010;Zhang et al, 2011) and equine sperm quality (Samper, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic factors influence on production and sperm quality have been reported by several studies (Kim et al, 1988;Fries, 1989). Dai et al (2009) and Dai et al (2011) examined the gene polymorphism FSH beta-sub unit of production and sperm quality in Simmental, Charolais and Limousin. Some researchers also associate the diversity of FSH beta-sub unit genes with litter size in sow (Yaofeng et al, 1998;Li et al, 2000;Li et al, 2008;Liu et al, 2009), sperm quality in boar (Wimmer et al, 2005;Lin et al, 2006), litter size in ewes (Xiaopeng et al, 2010;Zhang et al, 2011) and equine sperm quality (Samper, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that bulls carrying numerous naturally occurring mutations in the 5 0 -upstream regulatory region (5 0 -URR) of FSHB (c.-1166G>A, c.-1539_-1538delGGinsTTAACT, c.-1596C>A, c.-1724C>A and c.-1778C>A) had poor-quality semen, low fertility and reduced serum FSH levels compared with those without such mutations (Dai et al 2009). In addition, two different FSHB transcripts resulting from 23 linked mutations of genomic DNA have been identified in mutationbearing bull pituitaries (Dai et al 2011). However, the underlying mechanism that is involved is still unclear.…”
mentioning
confidence: 99%